Interviewing for Language Proficiency : Interaction and Interpretation - Ross, Steven J. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book analyses oral proficiency interviews, a mainstay of second language speaking proficiency assessment for several decades. Adopting a mixed-method perspective involving micro-analytic approaches, discourse analysis and quantitative methods such as multi-level modeling and event history analysis, the author focuses on interaction and discourse processes common in language assessment interviews. This innovative book will appeal to students and scholars of language assessment, conversation and discourse analysts, as well as practitioners and providers of oral proficiency assessment. Steven J. Ross is Professor of Second Language Acquisition at the University of Maryland, USA. He has served on the editorial boards of several journals, and was an Associate Editor of Language Learning 2011-2016. He has been Director of Training for the Language Proficiency Interview at the Institute for International Business Communication in Tokyo, and has taught research methods and language assessment in Japan, Mexico, Australia, and the USA.
Keywords: Linguistics.; Applied linguistics.; English language.; Discourse analysis.; Multilingualism.; Language and education.; Language and languages -- Study and teaching.; elektronické knihy; electronic books